Nilai Panen Cempe (Kid Crop) Kambing Kacang (Capra hircus) di Kabupaten Konawe Utara (Studi Kasus) - Saili, Takdir (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2014)
One of determined variable to evaluate population growth of livestock in certain area is the number of offspring produced in certain period. On goat and lamb production, productivity could be determined using kid crop variable.  Information related to kid crop, especially kid crop of Kacang goat in Konawe Utara District was limited, hence the research on this issue was need for providing the related data. The objective of this research was to determine kid crop of Kacang goat in Konawe Utara District. The location was sequentially established using stratified and purposive sampling methods, while respondent on the named village was established using counting method.  The results  showed  that  kid  crop of Kacang goat  in Konawe Utara District was 167,71% with 8,61 month of kidding interval and 1,36 kids of litter size,  whereas  mortality was    13,96%.  In  conclusion,  Kambing goat  productivity in Konawe Utara District was still good based on the kid crop variable.     Key word: Kacang goat, kid, kid crop, Konawe Utara.